TINGKAT PENGUASAAN KOMPETENSI PEDAGOGIK DOSEN NON KEPENDIDIKAN STAIN (Studi Kasus di STAIN Pekalongan dan STAIN Purwokerto) - Zaenal Mustakim (Jurnal Penelitian, 2013)
Higher education is one of the educational institutions that assist to realize the constitution mandate: to educate national citizen. Therefore, the lecturers as human resources of a college should have a reliable competence in order to support the realization of quality education. One of the competencies that should be possessed by the lecturer is pedagogic competence: their capability in understanding the foundation of education; understanding of the students; developing syllabus or curriculum; and managing the course. This study focused on: (1) the proficiency of STAIN Pekalongan’s non-trained lecturers at pedagogic competence; (2) the proficiency of STAIN Purwokerto’s nontrained lecturers at pedagogic competence. The results of this study showed that the proficiency of the non-trained lecturers of both STAIN Pekalongan and STAIN Purwokerto at pedagogic competence were still low. 21.55% of the non-trained lecturers of STAIN Pekalongan were proficient, 33.62% were less proficient, and 44.83% were not proficient. While at STAIN Purwokerto, 31.90% of its non-trained lecturers were proficient, 25.47% were less proficient, and 42.63% were not proficient. Overall, 26.72% of them (both those of STAIN Pekalongan and STAIN Purwokerto) were proficient, 29.55% were less proficient, and 43.73% were not proficient.